2006
DOI: 10.1097/01.shk.0000225863.56714.96
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocytic Apoptosis Following Global Cardiac Ischemia and Reperfusion Can Be Attenuated by Peroxisome Proliferator-Activated Receptor Α but Not Γ Activators

Abstract: In this study, experiments were designed to determine if peroxisome proliferator-activated receptor (PPAR) alpha agonists could decrease myocardial ischemia/reperfusion injury after cardioplegia-induced cardiac arrest under cardiopulmonary bypass, attenuate the appearance of cardiomyocytic apoptosis, and decrease the damage of reactive oxygen species. Cardiomyocytic apoptosis occurs after cardiopulmonary bypass surgery. Reactive oxygen species and peroxynitrite generated during ischemia/reperfusion initiate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 27 publications
3
41
1
Order By: Relevance
“…It was observed during analysis that 2-5% myocytes at the most demonstrated TUNEL positive nuclei by 7 days post-sepsis. These data are consistent with an in vivo study, in which 8% apoptotic nuclei were reported in a global cardiac ischemia reperfusion injury model in the rabbit (Yeh et al, 2006). An increased immunofluorescence of caspase-3 distributed throughout the cell cytosol was observed in the septic LV sections.…”
Section: Signaling and Apoptosis Mechanisms During Simdsupporting
confidence: 82%
“…It was observed during analysis that 2-5% myocytes at the most demonstrated TUNEL positive nuclei by 7 days post-sepsis. These data are consistent with an in vivo study, in which 8% apoptotic nuclei were reported in a global cardiac ischemia reperfusion injury model in the rabbit (Yeh et al, 2006). An increased immunofluorescence of caspase-3 distributed throughout the cell cytosol was observed in the septic LV sections.…”
Section: Signaling and Apoptosis Mechanisms During Simdsupporting
confidence: 82%
“…31,32 Fenofibrate, PPAR-a agonist, was proved effective in reducing the generation of ROS, overexpression of TNF-a, and excess NO production observed with oxidative and inflammatory tissue injuries. 10,17,33 The antioxidant and anti-inflammatory effects of fenofibrate are related to its ability to suppress the protein expression for NADPH oxidase, TNF-a, and inducible nitric oxide synthase by inhibiting the phosphorylation of p38 MAPK (mitogen-activated protein kinase). Fenofibrate, therefore, prevents the activation of the nuclear factor-kB signaling pathway, which promotes the transcription of NADPH oxidase, TNF-a, and inducible nitric oxide synthase genes.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn elevates EET levels, which mediate blood vessel dilation and lowers blood pressure (BP), especially in the setting of hypertension (2,3). Diverse sEH inhibitors limit injury in a variety of diseases (4), providing broad cardiovascular protection (5) against hypertension (6,7), ischemia and reperfusion injury (8,9), hypertrophy, and heart failure (10), as well as inflammation (11,12). Consistent with the therapeutic potential of hydrolase inhibitors, sEH null mice are protected from pathological interventions (13).…”
mentioning
confidence: 99%